2010
DOI: 10.1073/pnas.1008866107
|View full text |Cite
|
Sign up to set email alerts
|

Elementary steps at the surface of ice crystals visualized by advanced optical microscopy

Abstract: Due to the abundance of ice on earth, the phase transition of ice plays crucially important roles in various phenomena in nature. Hence, the molecular-level understanding of ice crystal surfaces holds the key to unlocking the secrets of a number of fields. In this study we demonstrate, by laser confocal microscopy combined with differential interference contrast microscopy, that elementary steps (the growing ends of ubiquitous molecular layers with the minimum height) of ice crystals and their dynamic behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
154
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(162 citation statements)
references
References 46 publications
8
154
0
Order By: Relevance
“…Hence, the β-QLL cannot be a solid phase but is a quasi-liquid phase appearing below 0°C. In the second case, the β-QLL has to be easily deformed by the lateral movement of elementary steps that are only 0.37 nm thick (7). Such an easily deformed phase would be a quasi liquid, rather than a solid, although at present the rigidity of a solid ice film of nanometer thickness is unclear.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the β-QLL cannot be a solid phase but is a quasi-liquid phase appearing below 0°C. In the second case, the β-QLL has to be easily deformed by the lateral movement of elementary steps that are only 0.37 nm thick (7). Such an easily deformed phase would be a quasi liquid, rather than a solid, although at present the rigidity of a solid ice film of nanometer thickness is unclear.…”
Section: Resultsmentioning
confidence: 99%
“…We attached a confocal system (FV300; Olympus Corporation) to an inverted optical microscope (IX70; Olympus Corporation), as previously explained (6,7). A superluminescent diode (Amonics Ltd.; model ASLD68-050-B-FA: 680 nm) and a He-Ne laser (Melles Griot 05-LHP-991: 633 nm) were used for LCM-DIM and interferometric observations, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, evidence of dissolution of the f010g face in contact with water sample Naica-08 was found at 45°C (during an experimental run of 20 h the opening of an etch pit on the f010g face was observed). Currently we are precisely determining the dissolution temperature interval for gypsum in Naica waters with laser confocal differential interference contrast microscopy (3,22). Although growth of gypsum crystals above 60°C in the Naica caves is very unlikely, normal growth rates were also measured at: 65, 70, 80, and 90°C because additional measurements should allow a better fit of the growth rates in the temperature range of interest (50-60°C, see next section).…”
Section: Geologymentioning
confidence: 99%
“…Before and after the single-molecule visualization, the surface morphology of a monoclinic HEWL crystal ( Figure 3a) was observed by laser confocal microscopy combined with differential interference contrast microscopy (LCM-DIM), by which at first elementary steps on protein crystal surfaces (several nanometers in height) 14 and later elementary steps on ice crystal surfaces (0.37 nm in height) 15 can be visualized with sufficient contrast. From the in situ observation of elementary steps on a monoclinic HEWL crystal by LCM-DIM, we confirmed that elementary steps were not proceeding or receding, proving that a crystal had been maintained in the equilibrium condition during the single-molecule visualization.…”
Section: Methodsmentioning
confidence: 99%